1999
DOI: 10.1016/s0735-1097(98)00680-9
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and efficacy of carvedilol in patients with New York Heart Association class IV heart failure

Abstract: Patients with chronic NYHA class IV heart failure are more likely to develop adverse events during initiation and dose titration when compared with less symptomatic patients but are more likely to show symptomatic improvement in the long term. We conclude that carvedilol is a useful adjunctive therapy for patients with NYHA class IV heart failure; however, they require close observation during initiation and titration of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
1
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 26 publications
0
63
1
6
Order By: Relevance
“…Recent data suggest that h-blockers are well tolerated in the elderly, 7 yet target doses may be difficult to achieve in certain subgroups, such as patients with low blood pressure (BP) and those with advanced disease. [8][9][10] In turn, prescription of low doses may raise concerns over efficacy because older patients may respond differently to medication. 11 In patients with HF, one randomized trial has shown that h-blockade produces a dose-dependent improvement in survival.…”
mentioning
confidence: 99%
“…Recent data suggest that h-blockers are well tolerated in the elderly, 7 yet target doses may be difficult to achieve in certain subgroups, such as patients with low blood pressure (BP) and those with advanced disease. [8][9][10] In turn, prescription of low doses may raise concerns over efficacy because older patients may respond differently to medication. 11 In patients with HF, one randomized trial has shown that h-blockade produces a dose-dependent improvement in survival.…”
mentioning
confidence: 99%
“…This increase in usage is likely to have conferred increased survival benefits in the newer trials, independent of aldosterone antagonist use. This has been demonstrated in two large trials published since 2000: the Carvedilol Post-Infarct Survival Control in Left Ventricular Dysfunction (CAPRICORN) study showed a 23% risk reduction in all-cause mortality and reductions in CV mortality and non-fatal reinfarction, 111 and the Metoprolol CR/ XL Randomized Intervention Trial in Heart Failure (MERIT-HF) showed similar significant reductions in patients with severe LVSD postMI. 112 Compounding this effect is the advancement in beta-blocker development, with the more recent trials benefiting from the availability of thirdgeneration beta-blockers that provide vasodilatory effects independent of beta-blockade.…”
Section: Exchangeabilitymentioning
confidence: 85%
“…Vale ressaltar, entretanto, que também com estas drogas, o início da terapêutica pode ser tormentosa. Recente estudo demonstrou que somente 50% dos pacientes em CF IV toleraram a droga 49 .…”
Section: Tratamento Clínicounclassified